Literary experience and communication in Georges Bataille - Ferreira, Silvia Raimundi (2020)
The desire of communicating the experience guided Georges Bataille’s oeuvre, his literary writing - both philosophical essays and erotic writings - was devoted using the project of expressing throughout language what is beyond the domain of language. His intention to communicate the real, the idea of touching with words the definitive moments of life, appears in his texts with the explicit purpose of taking the reader on a journey to the extreme, a journey that breaks the traditional limits of thinking and writing, in a communication that would happen through excess. Georges Bataille faced the chasm that lies in the heterogeneity of these structures - experience and language, and, like other authors, allows us today to question both the problem of representation and communication in literary language and the mystery surrounding the ability that art has to conciliate elements in a artwork that can convey what is not there. This article aims to search for meaningful elements of this discussion in the romance My Mother, approaching those exemples in a comparative way with the notions of desire and interdicted proposed by the psychoanalyst.